Industrial Revitalization with AI between Opportunities and Challenges for Global Economic Growth - Loso Judijanto; Asfahani Asfahani; Anjana Prusty; Nova Krisnawati; Asri Ady Bakri (Edujavare Publishing, 2025)
This study investigates the Industrial Revitalization with AI, exploring both the opportunities and challenges it presents for global economic growth. The aim is to provide a comprehensive understanding of AI's role in reshaping industries, the methods used in the study include qualitative research methods such as in-depth interviews with industry leaders, technology experts, and stakeholders. The findings highlight the significant potential of AI in enhancing productivity and innovation across various sectors, while also emphasizing the need for addressing concerns such as job displacement, data privacy, and regulatory frameworks. In conclusion, the study underscores the transformative impact of AI on industrial revitalization, emphasizing the importance of responsible AI deployment and collaborative efforts for sustainable economic growth.